Design, Fabrication, and Characterization of a Flexible Dual-Band Metamaterial Absorber - Wang Xin; Zhang Binzhen; Wang Wanjun; Wang Junlin; Duan Junping (IEEE Photonics Journal)
This paper presents the theory, design, simulation, fabrication, and performance of a flexible dual-band MM absorber, which is resonant at microwave frequencies. The sandwich structure of the MM absorber is composed of the periodic array of the T-shaped metallic patches and a continuous metallic plane, which are separated by a middle flexible dielectric layer. The optimized geometric parameters were obtained by numerous simulations using the full wave finite integration technology of CST 2015. The simulated results indicate that the proposed MM absorber has two distinct absorption peaks at 16.77 and 30.92 GHz with the absorption ratio of 98.7% and 99.3%, respectively. The absorber has a thickness of 0.2403 mm, which is only 1/74 and 1/40 of the wavelength for the resonance frequency of 16.77 and 30.92 GHz. The influence of the material's properties and structural curvature on the absorption performance was investigated by numerous simulations. The proposed MM absorber is highly sensitive to the polarization of the incidence EM wave and has good absorption properties over a large range of the incidence angle for the incidence EM wave. The electric field and surface current distributions at two independent resonance frequencies were analyzed for providing insight into the EM wave absorption mechanism. Simulated results show that two different resonance modes are introduced into the single patterned metallic resonance structure to realize the dual-band performance. The laser ablation process was adopted to fabricate the sample of the proposed absorber. Measured results for the normally incident EM wave show an agreement with the simulated results. The fabricated MM absorber shows significant mechanical flexibility and can easily be conformed to the unusual surfaces such as cylindrical, pyramid, and spherical. Furthermore, this design concept can be extended to the other absorber structure and the other frequency bands, therefore, which can greatly enrich the applications in antenna, sensing, thermal image, and detection. For instance, in the design of projectile-borne conformal antenna array, a flexible ultrathin MM absorber can easily be loaded between the antenna and the projectile body to reduce the radiation interference, weaken the coupling loss, and reduce the RCS.